(untitled) (Journal of Civil Engineering Researchers, 2025)
The primary aim of this article is the identification and selection of the optimal strategy for the exit of a significant capital volume invested in the construction of commercial centers in the face of investment risk in the construction of commercial complexes, along with influential factors in challenging economic conditions such as exchange rate fluctuations, transregional power sanctions, stagflation, excessive supply and growth in commercial complex construction in the country, etc., specifically focused on the Royal Mall Kish project. Indeed, the effectiveness and reliability of formulating and selecting exit strategies based on successful implementation and the creation of a sustainable economic cycle for a commercial complex are deemed essential and prerequisite. The research method employed is qualitative. In the qualitative section of this study, through interviews, we identified the relevant factors affecting exit strategies, considering the current conditions and business environment to achieve ultimate goals. These factors are ultimately categorized into three dimensions: structural, behavioral, and contextual. The qualitative sample population includes active experts in this project. At theoretical saturation point, 8 experts were identified as participants in the research. Ultimately, 43 influential components on strategy selection and 5 exit strategies were identified in this project that can be determined as suitable strategies in the appropriate situation for decision-making regarding exit.